Diagnosis of Pulmonary Embolism with d-Dimer Adjusted to Clinical Probability - Kearon, Clive; de Wit, Kerstin; Parpia, Sameer; Schulman, Sam; Afilalo, Marc; Hirsch, Andrew; Spencer, Frederick A; Sharma, Sangita; D’Aragon, Frédérick; Deshaies, Jean-François; Le Gal, Gregoire; Lazo-Langner, Alejandro; et al. (The New England journal of medicine, 2019)
Among patients with a low clinical pretest probability of pulmonary embolism and a d -dimer level of less than 1000 ng per milliliter (twice the usual threshold used to rule out the disorder), the need for diagnostic imaging was reduced from 51.9% to 34.3% of patients, without increasing the risk of missing the diagnosis of pulmonary embolism.